Bentonite as a natural additive for lime and lime–metakaolin mortars used for restoration of adobe buildings. (July 2015) - Andrejkovičová, S.; Alves, C.; Velosa, A.; Rocha, F.
Abstract: This work estimates the behaviour of mortars based on lime, seeking their application as renders of adobe walls. Mortars with binder:aggregate 1:3 volumetric ratio were prepared as is traditionally used in old buildings in central parts of Portugal. Due to specificity of the support, two clays, natural clay bentonite (5 wt.%) and artificial clay metakaolin (20 wt.%) were used as additives to lime mortar to prepare 3 types of blended mortars, besides the air lime reference mortar. Mortar prisms 4 × 4 × 16 cm were analysed to assess mechanical properties and salt resistance. Moreover, the mortars were placed in three ways on old adobes taken from demolished houses and their behaviour was verified by artificial accelerated ageing test. Lastly, mortars were applied on a wall made from traditional adobes, where panels were monitored and trials with adhesion strength and Karsten tubes have been conducted. The results obtained by comparison of the characteristics from all the experimental procedures reveal that mortar containing air lime and 5 wt.% of bentonite fulfils in the best way the requirements in its use as render of adobe buildings.